Acoustic emission-based diagnosis for valve faults in reciprocating compressor - Salah Mahdi Ali Al-Obaidi, 1984-, author; Mohd. Salman Leong, 1954-, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2016